Pengaruh Motivasi Prestasi Menurut David Mcclelland Terhadap Prestasi Akademik Siswa Dalam Pembelajaran PAI Kelas XI AKL Di SMK Ciledug Al-Musaddadiyah Garut - Raito, Raito; Nurul Baety, Putri (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
The learning process is a core activity within schools, and the act of learning continues throughout a person’s lifetime. Achieving optimal learning outcomes necessitates the presence of supportive factors, one of which is motivation. Motivation is the fundamental drive that propels an individual to act; without it, the learning process cannot yield maximum results. This study aims to explore David McClelland's motivation theory and its application within Islamic Religious Education (PAI). McClelland's theory focuses on three primary needs: the need for achievement, the need for power, and the need for affiliation. The research employs a descriptive method with a quantitative approach, gathering data or information on the observed phenomena. A total of 25 eleventh-grade students from the Accounting and Financial Institution (AKL) class at SMK Ciledug Al-Musaddadiyah Garut were sampled for this study. The initial hypothesis posited that r XY = 0 (no influence of David McClelland’s motivation on students' academic achievement), while the working hypothesis posited r XY ≠ 0 (there is an influence of David McClelland’s motivation on students' academic achievement). The results indicate that David McClelland’s achievement motivation significantly influences academic achievement in PAI learning by 69.75% among the eleventh-grade AKL students at SMK Ciledug Al-Musaddadiyah Garut, particularly in terms of the need for achievement. Keywords: David McClelland, motivation, academic achievement